2021
DOI: 10.3390/molecules26082267
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and Antioxidant Activity in Oat-Buckwheat Dough and Cookies with Added Spices or Herbs

Abstract: The aim of this study was to determine the phytochemicals and antioxidant activity in oat-buckwheat doughs and cookies with the addition of ten selected spices or herbs (2 g/100 g flours weight basis). The used spices and herbs, as was expected, showed a wide range of bioactive molecules, namely phenolic acids and flavonoids, and they are a rich source of components with antioxidant potential. All analysed oat-buckwheat dough showed higher antioxidant activity potential and higher total phenolic content (TPC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…(2022) investigated the extraction and antioxidant capacity of Medicago sativa and found the total antioxidant capacity under the optimized conditions 15.76 mg/g and 28.79 μmol Trolox/g. Starowicz et al. (2021) measured the antioxidant capacity in different plant species of which clover, related to lucerne have 873.00 ± 35.98 and 20.62 ± 0.72 μmol Trolox/g DM for ACW and ACL respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(2022) investigated the extraction and antioxidant capacity of Medicago sativa and found the total antioxidant capacity under the optimized conditions 15.76 mg/g and 28.79 μmol Trolox/g. Starowicz et al. (2021) measured the antioxidant capacity in different plant species of which clover, related to lucerne have 873.00 ± 35.98 and 20.62 ± 0.72 μmol Trolox/g DM for ACW and ACL respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Physiologically active ingredients of oats include vitamin E, carotenoids, anthocyanins, lignans, phytic acid, phenolics, and phytosterol, and Avn, which is a phenol present only in oats [ 81 , 82 ]. These components are secondary metabolites produced as defense mechanisms during plant growth and act as antioxidants that control cell damage from oxidative stress by removing reactive oxygen species in the human body [ 82 , 83 , 84 , 85 ]. Furthermore, the addition of oat components during the processing of food products helps to suppress fatty acid plaque development because of its antioxidant action and improves storage properties [ 23 , 86 , 87 ].…”
Section: Other Bioactive Ingredients and Functionalitiesmentioning
confidence: 99%
“…On the other hand, oats possess a high level of dietary fiber and carbohydrates, predominantly consisting of unsaturated fats. Both crops present various nutritional advantages and make a valuable contribution to enhancing human health . It was demonstrated that adding oat flour significantly increased β-glucan levels, resulting in lower postprandial blood glucose levels compared to wheat flour alone ( p < 0.05) .…”
Section: Introductionmentioning
confidence: 99%